Relationship between the rule of law and the principle of legality - Bratasiuk, Mariia; Rosoliak, Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article deals with the problem of correlation between the principles of rule of law and the principle of legality. The necessity of considering this problem from the standpoint of natural-legal doctrine is emphasized. It is emphasized that the rule of law principle is a megaprinciple, the content of which is the principle of legal legality.